KAJIAN DIKSI DAN PENCITRAAN DALAM CERPEN CINTA LAKI-LAKI BIASA KARYA ASMA NADIA - Doni Uji Windiatmoko (Indonesian language and literature education program Majapahit Islamic University, 2024)
The aim of this research is to describe the diction and imagery contained in the novel Cinta Men Ordinary by Asma Nadia. The research method uses a qualitative descriptive method. The data and data sources were taken from the novel text. The data collection technique uses the listening and note-taking method and the data analysis technique uses content analysis. The research results that can be described are that there are aspects of diction or denotative word choice totaling six (6) words; connotative, consisting of four (4) words; a typical greeting consisting of three (3) words; is a loanword consisting of two (2) words; two (2) words in the nature of foreign words; In regional language there are two (2) words. Meanwhile, the imaging aspects found were seven (7) elements of vision; in the form of five (5) hearing elements; in the form of one (1) touch element; in the form of four (4) flavor elements; in the form of two (2) elements of smell, in the form of four (4) movement elements. Keywords : Diction, imagery, novel